Do Leptin Play a Role in Metabolism–Related Psychopathological Symptoms? - Zhang, Yelei; Li, Xiaoyue; Yao, Xianhu; Yang, Yating; Ning, Xiaoshuai; Zhao, Tongtong; Xia, Lei; Zhang, Yulong; Zhang, Kai; Liu, Huanzhong (Frontiers in Psychiatry, 2021)
Objectives:Leptin is a crucial regulator of energy balance and is associated with obesity. In recent years, it has also been recognized as a psychopathological mechanism. Our study aimed to elucidate the relationships between serum leptin levels, body mass index (BMI), and psychopathology symptoms in patients with schizophrenia. Methods: A cross-sectional assessment of 324 inpatients with schizophrenia was conducted. Schizophrenia symptoms were measured using the Positive and Negative Syndrome Scale (PANSS) and the Brief Psychiatric Rating Scale (BPRS). Serum leptin levels were assessed by the Enzyme-Linked Immunosorbent Assay (ELISA). Results: Significant differences in sex, BMI, and negative symptom subscale (PANSS-N) scores were found between the groups with high and low leptin levels in the study. Leptin levels were positively correlated with BMI (B=2.322, t=9.557, P<0.001) and negatively correlated with PANSS-N scores (B=-0.303, t=-2.784, P=0.006). Conclusions:Our results suggest that the increase in leptin levels is responsible for antipsychotic-induced weight gain and improved psychopathological symptoms.